Protection Registration Parameters for Legal Protection of Geographical Indication Products Against Combination Factors (Natural Factors with Human Factors) - Apriliani, Kadek; Putu Angga Pratama Sukma; I Made Sudirga (Faculty of Law, Universitas Pekalongan, 2024)
The research aims to explore the impact of geographical indications on increasing the value of products or commodities, thereby boosting the economy of the region where the geographical indications originate. This focus is directed towards the producers rather than the farmers (protecting the communal society) and adheres to the